Using Population Dynamics to Model Harvest Regulation Impacts to Channel Catfish in the Monongahela River, West Virginia. (25th May 2021) - Chestnut‐Faull, Kristen L.; Phelps, Quinton E.; Smith, Dustin M.; Wellman, David I.
Abstract: Channel Catfish Ictalurus punctatus were collected during 2018 and 2019 from the Monongahela River in West Virginia using hoop nets to estimate population dynamics. Length, weight, sex, fecundity, and age data were obtained from collected individuals. Population characteristics (e.g., relative abundance, size structure, age structure, growth, etc.) were modeled under three proposed length limits of 300, 375, and 450 mm. Simulation results indicated that growth overfishing may occur when exploitation rates reach 36% under a 300‐mm minimum length limit. Furthermore, recruitment overfishing began to occur at 40% exploitation under a 300‐mm minimum length limit. Additionally, simulations suggest that no recruitment or growth overfishing occur at minimum length limits of 375 mm or 450 mm until extremely high exploitation levels (>90%) are reached. Thus, future consideration should be given for implementation of a 375‐mm minimum length limit of Channel Catfish in the Monongahela River to prevent growth and recruitment overfishing while also ensuring anglers are still able to harvest Channel Catfish.